Thermal decomposition of ammonium metavanadate - Stewart, Brian Victor (Rhodes University, Faculty of Science, Department of Chemistry, 1972)
The isothermal, endothermic, stepwise decomposition of ammonium metavanadate (AMV) in inert (argon or nitrogen), oxidising (air or oxygen) and reducing (ammonia) atmospheres as well as under high vacuum (pressure < IOn bar) conditions has been investigated. The reverse reaction, the isothermal recombination of V₂ 0₅ with ammonia and water vapour has also been investigated. The decomposition and recombination reactions were followed by continuously recording the mass loss of the sample with time using a Cahn R.G. Automatic Electrobalance. This enabled small samples ( ~ lOmg) to be used and consequently any self cooling of the sample during the decomposition was minimized. The intermediates and final products formed have been characterized by chemical analysis, X-ray powder diffraction studies, infrared spectroscopy and the mass loss involved in their formation. The changes in the physical properties of the samples during decomposition and recombination have been investigated by surface area measurements (using the BET method and krypton adsorption) and eIectron microscopy. Values for the enthalpy changes involved in the decomposition have been obtained by differential scanning calorimetry. The stoichiometry of the isothermal decomposition of ammonium metavanadate, under the various conditions of surrounding atmosphere has been discussed. Except for the later stages of the decomposition in ammonia, the results correspond well to the gradual reduction of the ratio of "(NH₄)₂ 0" to "V₂0₅" units from the original 1:1 ratio in ammonium metavanadate to pure "V₂0₅" with ammonia and water being evolved throughout the decomposition in the mole ratio of 2:1. The final product of the decomposition in vacuum, argon and air is "V₂0₅" and in ammonia, below 360°, V0₂. The kinetic parameters for each of the stages of the decomposition of AMV in each of the atmospheres studied have been determined. The mechanism of the first stage of the decomposition under the different conditions of surrounding atmosphere has been discussed from both the kinetic and the thermodynamic points of view. The absolute reaction rate theory has been applied to the decomposition in inert atmospheres enabling the formulae of the activated complexes formed during each stage to be calculated. It has also been shown that the detailed atomic movements occurring during the first stage of the decomposition in ammonia can be predicted from a knowledge of the stoichiometry of the reaction and of the detailed crystal structures of the starting and product materials. The kinetics and mechanism of the recombination of "V₂0₅" with ammonia and water vapour to form AMV have also been discussed in detail.
Keywords: Decomposition (Chemistry); Solids -- Thermal properties; Ammonia